CPA Examination: Auditing. - Meigs, Walter B. (The Accounting Review, 1965)
The auditing section of the May 1965 Uniform Certified Public Accountants examination was given on May 13, 1965 from 8:30 to 12:00 noon. The first section of the examination consisted of six questions, all required; the second section contained two questions of which the candidate was instructed to answer the one of his choice.